2022
DOI: 10.46582/jsrm.1801003
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Vascular Fraction for Knee Osteoarthritis – An Update

Abstract: Orthobiologics never cease to cause popularity within the medical science field, distinctly in regenerative medicine. Recently, adipose tissue has been an object of interest for many researchers and medical experts due to the fact that it represents a novel and potential cell source for tissue engineering and regenerative medicine purposes. Stromal vascular fraction (SVF), for instance, which is an adipose tissue-derivative, has generated optimistic results in many scenarios. Its biological potential can be ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“… 58 Histologic analysis in human studies revealed that fat grafting may increase vascularity, new collagen deposition and reorganization. 63 Piccolo et al showed improved wound healing and fibrosis in acute and subacute wounds. 64 ADSCs promote angiogenesis, regulate the inflammatory process, can differentiate into multiple cell types and secrete growth factors such as keratinocyte growth factor, vascular endothelial growth factor (VEGF), hepatocyte growth factor, fibroblast growth factor‐2, EGF and platelet‐derived growth factor.…”
Section: Products From Peripheral Blood – Prp and ...mentioning
confidence: 99%
See 1 more Smart Citation
“… 58 Histologic analysis in human studies revealed that fat grafting may increase vascularity, new collagen deposition and reorganization. 63 Piccolo et al showed improved wound healing and fibrosis in acute and subacute wounds. 64 ADSCs promote angiogenesis, regulate the inflammatory process, can differentiate into multiple cell types and secrete growth factors such as keratinocyte growth factor, vascular endothelial growth factor (VEGF), hepatocyte growth factor, fibroblast growth factor‐2, EGF and platelet‐derived growth factor.…”
Section: Products From Peripheral Blood – Prp and ...mentioning
confidence: 99%
“…According to the literature, these biological materials contain cytokines, mesenchymal and stem/progenitor cells. 18 …”
Section: Introductionmentioning
confidence: 99%
“…By definition, orthobiologics are organic or synthetic materials that promote enhanced healing of musculoskeletal disorders [9]. Many orthobiologic products have been discussed in the literature, including acellular solutions like hyaluronic acid (HA) and cellular alternatives such as platelet-rich plasma (PRP), injectable platelet-rich fibrin (i-PRF), bone marrow aspirate/bone marrow aspirate concentrate (BMA/BMAC) and adipose tissue derivatives [10][11][12][13][14]. These products can have autologous or allogeneic origins and are known to contain a rich secretome and a wide variety of cells with potent stimulatory effects [15].…”
Section: Gradementioning
confidence: 99%
“…Stromal vascular fraction contains paracrine factors that stimulate and enhance endogenic regenerative pathways [ 60 , 62 ]. Its biological and biomolecular action mechanisms include stimulation of angiogenesis, immune modulation, cell proliferation, and differentiation and extracellular matrix functionalization [ 63 ]. Isolation of AD-tSVF from the abdominal fat tissue is almost always possible in all patients.…”
Section: Adipose Derived Stromal Vascular Fraction (Ad-svf)mentioning
confidence: 99%